1986
DOI: 10.1111/j.1468-0092.1986.tb00360.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sealing Structures of Minoan Crete: Mm Ii Phaistos to the Destruction of the Palace of Knossos

Abstract: Summary. The thousands of MM clay sealings in Room 25 of the First Palace of Phaistos testify to the importation into Crete of the Near Eastern system of storeroom administrative controls. Minoan practice then diverged from the Near Eastern model. The development of a recognizably Minoan sealing system is illustrated by the LM IB sealing deposits from Ayia Triada, Zakro and Khania (with something of its evolution traceable via Mallia and Knossos). Despite many common practices in LM IB, however, important loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Imported and imitation scarabs and scaraboids were also well known in Minoan Crete (cf. Phillips , 106–34), and it has been suggested that Minoan sealing practices were inspired by Egypt and the Near East, whereby a multiplicity of sealing practices were employed (Weingarten ). Ben‐Shlomo (, 280) has observed that the conoid stamp seals were more suited to sealing a variety of objects than cylinder seals and that several Tel Miqne‐Ekron and Ashdod sealings produced two identical impressions.…”
Section: Philistine Ethnicitymentioning
confidence: 99%
“…Imported and imitation scarabs and scaraboids were also well known in Minoan Crete (cf. Phillips , 106–34), and it has been suggested that Minoan sealing practices were inspired by Egypt and the Near East, whereby a multiplicity of sealing practices were employed (Weingarten ). Ben‐Shlomo (, 280) has observed that the conoid stamp seals were more suited to sealing a variety of objects than cylinder seals and that several Tel Miqne‐Ekron and Ashdod sealings produced two identical impressions.…”
Section: Philistine Ethnicitymentioning
confidence: 99%
“…The study of Aegean sealing practices has traditionally focused on the decorative motifs and the iconography of engraved seals of bone, ivory, stone, or metal (e.g., Younger 1988; Aruz 1994; Dickers 2001; Krzyszkowska 2005; Anderson 2016; Davis and Stocker 2016; Stocker and Davis 2017). Additional studies have focused on clay sealings, although the primary interest has remained on those sealings impressed with iconographic representations and/or inscriptions (e.g., Pini 1964; Weingarten 1983; 1986; 1988; 2012; Palaima 1987; 1990; Hallager 2006; Younger 2012; Panagiotopoulos 2014). Rarely have sealings been studied for the information that they provide about Late Bronze Age storage practices more broadly defined, including the types of objects sealed and their role in international exchange, notable exceptions being Martha Wiencke's (Heath 1958; Wiencke 1969) detailed treatment of sealing practices at the House of Tiles at Lerna, Enrica Fiandra's (1968) work on the sealing practices at Protopalatial Phaistos, Ingo Pini's (1997) reexamination of the clay sealings from the Palace of Nestor and, most recently, Artemis Karnava's (2018) study of stamped sealings and nodules from Akrotiri.…”
Section: Past Scholarship On Aegean Sealing Practicesmentioning
confidence: 99%
“…The very limited Hieroglyphic and Linear A records of that date give little idea of the nature or scale of administration. The control over access to several storerooms documented by the abundant sealings from Phaistos (Weingarten 1986), need not represent a state-level administration, being anticipated by centuries in the sealing system in use at EHII Lerna. The scale of the Protopalatial palace structures themselves (Macdonald 2010;La Rosa 2010;Militello 2012), and the differentiated society they represent, support an assumption of state administration for their construction, maintenance, and the specialised activities they housed, but tell us little about their regional dominance or how they were organised or functioned.…”
Section: Defining Polities Through Administrative Evidencementioning
confidence: 99%
“…Turning to the Neopalatial period, where we have considerably more abundant evidence, the political interpretation of the administrative artefacts is far from clear. Differences in administrative practices have been well documented, particularly between Haghia Triadha and Zakros, the two sites with substantial samples of administrative artefacts (Weingarten 1986;Hallager 1996;Schoep 1999). Unfortunately, these assemblages largely represent different types of specialised administrative activities, and are not directly comparable for an assessment of differences in overall administrative practices; they simply emphasise how partial our evidence is for administration at each site.…”
Section: Defining Polities Through Administrative Evidencementioning
confidence: 99%
See 1 more Smart Citation